The Role Of Employee Turnover Between Employee Job Satisfaction And Company Performance In The Penang Automation Industry. - Marisoosay, Santhanadass (2009)
The semiconductor and electronics industries are the leading manufacturing sectors in all industrialized and industrializing countries of the world. Automation is a vital part of these industries. Automation is becoming a must for a country to focus in if they wanted to be involved in semiconductor or electronics industry. There are many automation companies in Malaysia which belong to either Malaysian or foreign investors.